Efeitos de mudanças globais na fisiologia de haplótipos de Bostrychia spp. (Rhodophyta) de populações tropicais e subtropicais - Borburema, Henrique Douglas dos Santos (Universidade Federal do Rio Grande do Norte, 2022)
Global change due to the anthropogenic emissions of polluting gases into the Earth’s atmosphere is an ecologically serious problem. Primary producers in coastal ecosystems such as mangrove swamps can be negatively affected by the global changes. Thus, in this thesis, we investigated the physiology of the mangrove macroalgae Bostrychia montagnei and Bostrychia calliptera from tropical and subtropical populations after being subjected to global change experimental conditions. The genetic divergence between tropical and subtropical specimens was also investigated using mitochondrial (COI-5P) and plastidial (rbcL-3P) DNA markers. The results from our investigation are presented in five scientific articles, whose main results are described hereafter. In the first article (doi.org/10.1016/j.jembe.2022.151740), we reported that tropical specimens are genetically divergent from subtropical specimens, based on the COI-5P marker. We also demonstrated that macroalgae from both climatic niches are tolerant of decreased pH (7.6 and 7.2) by CO2 enrichment of the seawater (ocean acidification), increasing their growth under decreased pH treatments due to increased CO2 availability for photosynthesis. Tropical B. montagnei increased its polysaccharide and allophycocyanin content at pH 7.2, and subtropical B. montagnei increased its low molecular weight carbohydrate content at pH 7.2 as well. In the second article (doi.org/10.1016/j.marenvres.2022.105662), we reported that tropical and subtropical B. montagnei and B. calliptera decreased their growth and photosynthetic performance under simultaneous increase in temperature (ocean warming) and salinity. We evidenced that macroalgae synthesized proteins, carbohydrates and antioxidants to tolerate detrimental temperatures and salinities, as well as they adjusted their pigment contents (phycobiliproteins, carotenoids, and chlorophyll a) for efficient light-harvesting under thermal and saline stress. In the third article, we observed that tropical B. calliptera and B. montagnei ...